Haiyin Liang: capstone - Liang, Haiyin, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist, I grew up in China and traditional Chinese culture inspires my artwork. In this rapidly-developing society, Chinese people pay less attention to our traditional cultures and history. However, I believe it is important to carry forward our culture heritage, because it embodies the spirit of our nation. Particularly, traditional Chinese arts have a long history and hold the intelligence and ideals of the Chinese people. My artwork is associated with these traditional Chinese arts, and is informed by the styles and subjects of Chinese landscape painting and fine brushwork painting. I express the literary pursuits that ancient Chinese scholars always practiced, and place the viewer in a moment that has poetic and pictorial splendor. I aspire to bring elements of traditional Chinese art into contemporary metal and jewelry artworks to emphasize that Chinese art does not only speak to the past, but is culturally relevant in the present. Moreover, I enjoy the idea of fusing beauty with meaning to attract viewers' attention and move their hearts. I have taken forms from some objects that existed in China since the ancient period, such as a room screen, a fan, the Pipa (a traditional musical instrument); and using imagery that has special meanings in China, such as the crane, the phoenix and the plum. For example, the crane is a significant symbol in Chinese history that represents high loyalty, nobility and faithfulness. These symbols also embody personal cultivation. I emphasize the importance of personal cultivation because it not only relates to personal development but also connects and contributes to the thriving of a country and nation.
Ultramarine - beyond the sea
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing and jewelry